Helicobacter pylori protein that binds to and activates platelet specifically reacts with sera of H. pylori-associated chronic immune thrombocytopenia. (17th November 2021) - Takeuchi, Hiroaki; Islam, Jahirul Md; Kaneko, Ayami; Kimura, Asako; Shida, Takashi; Oboshi, Wataru; Katayama, Hironori; Oishi, Taku; Fujieda, Mikiya; Morimoto, Norihito
Abstract: Immune thrombocytopenia (ITP) is an acquired autoimmune disorder characterized by antiplatelet antibodies and/or CD8 + T cells, resulting in the destruction of platelets and decreased platelet counts. Helicobacter pylori that persistently colonizes the stomach causes various disorders, including extragastric diseases such as chronic ITP (cITP). Several studies have reported increased platelet counts in H. pylori -infected cITP patients with eradication treatment and also the pathophysiological pathways involving cross-reaction of antibodies against H. pylori with platelets, the modulation of Fcrγ receptors balance and others. We previously reported an immunocomplex pathway comprising H. pylori low-molecular-weight (LMW) antigens, their antibodies, and platelets, involved in the development of H. pylori -associated cITP; however, the LMW antigens were not identified. In the present study, we demonstrated that the H. pylori LMW antigen of the immunocomplex was identified as Lpp20 of outer membrane proteins. Lpp20 could bind to platelets and specifically react with sera of H. pylori -associated cITP patients.